Evaluasi Kelayakan Investasi Proyek Pembangunan Perumahan Green Terrace Ditinjau pada Aspek Keuangan - Ilyas, Amin (Journal of Economics & Business UBS, 2020)
Indonesian population growth rate was quite high especially in regions jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). The resulted in increased demand for homes. Green Terrace Housing Project located in the street Mukti, Jati Asih, Bekasi, which was completed in 2013, contributing to the increase in demand for homes. Project finance is an information that can help investors to identify the feasibility of a project. One of the tools used in the analysis financial was capital budgeting. With the calculation method using NPV, IRR, and PI. Researchers use secondary data from PT Ritma Panca Gemilang, in form of cash flows during the project within a period, from 2009 to 2013. Results of the study were reviewed on the financial aspects through the method of calculation of Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). The Third calculation results showed good results, so the evaluation of capital budgeting Green Terrace housing development was feasible. The results of the study were reviewed through the financial aspects of capital budgeting methods bring out the Net Present Value (NPV) RP 7,286,398,008.25, Internal Rate of Return (IRR) with a 25% percentage, and Profitability Index (PI) 2,86. The calculation results indicate an ideal outcome, so the evaluation of capital budgeting of Green Terrace housing development was prope.